The Limits of Small-Scale Landlords: Binding Constraints to Residential Real Estate Investment Expansion - S. Romero, Reil; P. Tarpin, Charlene Lydia; M. Alcantara, Dona Mae; R. Roddilla , Edjelei (International Journal of Management and Education in Human Development, 2024)
The small-scale landlords in the private rented sector make a critical contribution to the supply of affordable residential accommodation to prospective tenants. However, small-scale landlords face several constraints, ensuing the shortage supply of affordable residential dwellings aggravated by the growing demand in the rental market. This phenomenological qualitative study explored the limiting constraints to residential real estate investment expansion of small-scale landlords operating in the Downtown area of Davao City. The researchers conducted face-to-face interviews with five small-scale landlords. Qualitative data was analyzed using the Delphi technique. From the data gathered, six main themes emerged, which are: (a) being business-minded with the opportunities; (b) making dwelling units available; (c) allocating income to expenditures; (d) investment decisions and financial challenges; (e) other regulatory and marketing limitations; and (f) long-term investment. Findings revealed that the most prevalent type of landlords in the area consisted of subsistence landlords. The results also showed that the most important factor is financial constraints, whereas the least important factor is building regulations. The implications of this study could be used to alleviate the perceived constraints of small-scale landlords toward investment expansion and, therefore, produce more residential properties that will significantly contribute to the supply of affordable rental accommodation.